PENGARUH GAYA KOMUNIKASI THE EQUALITARIAN STYLE PIMPINAN TERHADAP KINERJA PELAKSANA PROGRAM ACARA INSERT TRANS TV - Kusnul Arifin; Permadi Aji Pamungkas (Jurnal Pustaka Komunikasi, 2019)
The purpose of this study was to be able to explain the influence of the Communication Style "The Equalitarian Style" of the Leader on the performance of the implementers of the Insert Trans TV program. The sampling technique uses saturated sampling or census. The results of the study show that the performance of the Program Implementing Insert Trans TV employees is very good. This employee's performance is due to the ability to use work equipment so that they rarely make mistakes with little time. Employee performance is also generated from the existence of mutual cooperation between employees in overcoming work problems so that work spirit arises to do work effectively and efficiently; The results of the analysis of the influence of the Communication Style variable "The Equalitarian Style" Leaders on the performance of the implementers of the Insert Trans TV program are indicated by the coefficient of determination (rxy) of 0.199 = 19.9%. This shows that 19.9% of the variance in the performance variable of the employees of the Insert Trans TV program are determined by the Communication Style variable "The Equalitarian Style" of the Leader, and the rest (= 80.1%) is determined by other variables that cannot be explained in the study this.